Strategi Strategi Peningkatan Koperasi Dalam Meningkatkan Pertumbuhan Ekonomi: Cooperative Development Strategy to Increase Economic Growth - KINARO, MAIJON; Murtiana, Sri; Eko Saputro, Guntur (JSE: Jurnal Sharia Economica, 2025)
Cooperatives in Indonesia play a crucial role as the main drivers of the people's economy, particularly in supporting the welfare of members and the community. However, in the current digital era, cooperatives face increasingly complex challenges, such as limited access to technology and low-quality human resources. This research aims to identify effective strategies to enhance cooperatives' contribution to national economic growth using Arthur F. Lykke's strategic theory framework, which consists of three main elements: Ways (methods), Means (resources used), and Ends (goals to be achieved). By using a literature study method and analyzing 15 relevant scientific journals, this research finds that innovation in digitalization, capacity building of human resources, and strategic collaboration are key for cooperatives to transform and strengthen their competitiveness in the global market. The research results show that with the right strategy, cooperatives can become a major driving force in creating inclusive and sustainable economic growth, strengthening local economic resilience, and empowering communities towards better welfare.